The intricate anatomy of the periodontal ligament and its development: Lessons for periodontal regeneration - Jong, T.; Bakker, A. D.; Everts, V.; Smit, T. H. (Journal of periodontal research, 2017)
The periodontal ligament (PDL) connects the tooth root and alveolar bone. It is an aligned fibrous network that is interposed between, and anchored to, both mineralized surfaces. Periodontal disease is common and reduces the ability of the PDL to act as a shock absorber, a barrier for pathogens and a sensor of mastication. Although disease progression can be stopped, current therapies do not primarily focus on tissue regeneration. Functional regeneration of PDL may be achieved using innovative techniques, such as tissue engineering. However, the complex fibrillar architecture of the PDL, essential to withstand high forces, makes PDL tissue engineering very challenging. This challenge may be met by studying PDL anatomy and development. Understanding PDL anatomy, development and maintenance provides clues regarding the specific events that need to be mimicked for the formation of this intricate tissue. Owing to the specific composition of the PDL, which develops by self‐organization, a different approach than the typical combination of biomaterials, growth factors and regenerative cells is necessary for functional PDL engineering. Most specifically, the architecture of the new PDL to be formed does not need to be dictated by textured biomaterials but can emerge from the local mechanical loading conditions. Elastic hydrogels are optimal to fill the space properly between tooth and bone, may house cells and growth factors to enhance regeneration and allow self‐optimization by the alignment to local stresses. We suggest that cells and materials should be placed in a proper mechanical environment to initiate a process of self‐organization resulting in a functional architecture of the PDL.